Commute time and subjective well-being in urban China - Peng Nie; Alfonso Sousa-Poza (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
Using data from the 2010 China Family Panel Studies, this study investigates the association between commute time and subjective well-being in a sample of 16- to 65-year-old employees in urban China. We find evidence that a longer commute time is associated with lower levels of both life satisfaction and happiness, especially when the commute times are extreme (≥ 1 hour per day). A multiple mediation analysis further indicates that the relation between commute time and happiness is partially mediated by time spent on daily activities, particularly sleeping. We calculate the amount of income necessary to compensate an employee's loss in well-being at approximately 82 yuan per hour of commute time, implying that, in urban China, the annual loss of well-being amounts to around 10 billion yuan.
urn:nbn:de:bsz:100-opus-11484
Keywords: I31; J30; J33; R41; 330; commute time; life satisfaction; happiness; urban China